Pilot testing of fire sprinkler system in extremely corrosive industrial duct environments. Issue 3 (6th March 2013) - Su, Paul; Doerr, William W.; Harrington, J.C.; Fuller, David B.; Barna, Jon M.
<x xml:space="preserve">Abstract</x> Due to the extremely corrosive environments inside many exhaust ducts fabricated from combustible materials, the mechanical integrity of fire sprinkler system components is often prematurely compromised, leaving the system unable to protect against fires originating within these ducts [FM Global Loss Prevention Data Sheet, 7–78, Industrial Exhaust System, 2011; Understanding the Hazard, Fire in Industrial Exhaust Systems, FM Global, Johnston, RI, 2006]. Pilot testing of a new fire sprinkler system was conducted to protect the fiber‐reinforced plastic duct at a nitric/hydrofluoric (HF/HNO3) mixed acid pickling operation. Based on previous laboratory and field tests [Su and Doerr, Process Saf Prog 29 (2010) 70–78], this fire sprinkler system was composed of corrosion resistant sprinkler nozzles, a linear heat detector, flexible mounting connections, sprinkler piping, and controls. Pilot testing results have led to development and recommendation of a new fire protection system capable of protecting combustible exhaust ducts from fire in extremely corrosive environments. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 277–282, 2013